Ezra in Egypt?: The Significance of Hananyah’s Mission - Toorn, Karel van der (Vetus Testamentum, 2017)
The history of the Jewish community at Elephantine plays a crucial role in the reconstruction of the early history of Judaism. One document in particular sheds a light on the emerging Jewish identity in the diaspora. It is Hananyah’s so-called Passover Letter. This contribution investigates the significance of Hananyah’s mission in Egypt, and more particularly its relationship with the missions of Ezra and Nehemiah. The investigation permits three conclusions. One, the Persians did not distinguish between ethnicity and religion; two, the codification of Jewish ritual preceded the codification of the Torah; and three, Jewish identity in the late 5th century allowed significant latitude in matters of doctrine and lifestyle.